An intermittent pneumatic compression device reduces blood lactate concentrations more effectively than passive recovery after Wingate testing - Hanson, E.; Stetter, K.; Li, R.; Thomas, A. (Journal of Athletic Enhancement, 2013)
Study background: With the advancement of technology, therapeutic modalities mimicking "cool down" have become an option for active individuals to try and decrease the recovery time between training sessions and competition. A wide variety of companies that manufacture these modalities have claimed their machines can decrease recovery time by decreasing lactic acid, a known cause of muscle fatigue following exercise. The aim of this study was to investigate an intermittent pneumatic compression (IPC) unit as a recovery modality by evaluating its effectiveness in clearing blood lactate (BLa) when compared to alternate recovery methods following an anaerobic Wingate cycling test (WAnT).